2020
DOI: 10.18698/2542-1468-2020-6-96-102
|View full text |Cite
|
Sign up to set email alerts
|

Coniferous plants root system formation in plantations of Izhevsk (Udmurt Republic)

Abstract: A study of the root systems of tree species, their distribution in soil in horizontal and vertical directions, expressed by quantitative and qualitative indicators in the form of architectonics, underground phytomass, volume, surface, area and root saturation, answers many questions regarding the growth and development of tree plants. The growth conditions and species characteristics of plants have a significant effect on the formation of the root system.The studies were carried out in the large industrial cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is shown that there is a close dependence of ascorbic acids (АА) accumulation with the water status of plants and the SSD of the leaf, moreover, the direction of the correlation is reversed (Table 2). A number of scientists have noted a tendency to increase the synthesis of ascorbic acid in plants in an anthropogenic environment [22,28]. We have shown that the involvement of AA in protective reactions is genetically determined (Fig.…”
Section: Fig 1 the Content Of Pigments In The Leaves Of Maple Species...mentioning
confidence: 82%
See 2 more Smart Citations
“…It is shown that there is a close dependence of ascorbic acids (АА) accumulation with the water status of plants and the SSD of the leaf, moreover, the direction of the correlation is reversed (Table 2). A number of scientists have noted a tendency to increase the synthesis of ascorbic acid in plants in an anthropogenic environment [22,28]. We have shown that the involvement of AA in protective reactions is genetically determined (Fig.…”
Section: Fig 1 the Content Of Pigments In The Leaves Of Maple Species...mentioning
confidence: 82%
“…Adaptation to the conditions of the urban environment requires changes in the physiological and biochemical characteristics of plants as a mechanism of adaptive reactions to anthropogenic stresses [19]. One of the active agents that worsen the condition of plants in the city is atmospheric air pollution, which causes oppression of the leaf apparatus, due to blockage of stomata, and a decrease in photosynthetic ability [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, a major issue in the development of large cities is air pollution from both stationary (industrial enterprises) and mobile (vehicles) sources [1]. Plantations near urban areas largely influence air quality [2]. These forests play a major role in absorbing CO2 compounds produced by both vehicles and industrial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable development of the country, high quality of life, and health of the residents can be achieved only if natural systems are preserved, and the appropriate quality of the environment is maintained. One of the conditions for achieving sustainable development goals is to build a comfortable urban environment, where a significant role should be played by green areas [1].…”
Section: Introductionmentioning
confidence: 99%